2009
DOI: 10.1038/jcbfm.2009.5
|View full text |Cite
|
Sign up to set email alerts
|

Changes in Experimental Stroke Outcome across the Life Span

Abstract: Acute ischemic stroke is a leading cause of mortality and disability in the elderly. Age is the most important nonmodifiable risk factor for stroke, yet many preclinical models continue to examine only young male animals. It remains unclear how experimental stroke outcomes change with aging and with biologic sex. If sex differences are present, it is not known whether these reflect an intrinsic differing sensitivity to stroke or are secondary to the loss of estrogen with aging. We subjected both young and agin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

28
194
1
1

Year Published

2009
2009
2017
2017

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 198 publications
(224 citation statements)
references
References 48 publications
28
194
1
1
Order By: Relevance
“…Variation in plasma Cryab levels may be one of the several differences between younger and older patients to explain the worse outcome in older patients (33,34). Earlier studies have described Cryab as a guardian molecule in brain inflammation in multiple sclerosis, and this descriptive name clearly translates to its role in stroke (10,35).…”
Section: Discussionmentioning
confidence: 99%
“…Variation in plasma Cryab levels may be one of the several differences between younger and older patients to explain the worse outcome in older patients (33,34). Earlier studies have described Cryab as a guardian molecule in brain inflammation in multiple sclerosis, and this descriptive name clearly translates to its role in stroke (10,35).…”
Section: Discussionmentioning
confidence: 99%
“…Most experimental stroke studies have been performed on young animals, and therefore may not fully replicate the effects of ischemia on neural tissue in aged subjects. Aged male mice have less histological damage after MCAO despite increased functional deficits and mortality, the underlying mechanism of which remains elusive (Liu et al 2009b). Recent studies have demonstrated that aging is accompanied by an increase in AMP/ ATP ratio in multiple tissues (Hardie and Hawley 2001;Petersen et al 2003;Wang et al 2003), yet AMPK levels are surprisingly lower in aged muscle (Qiang et al 2007;Reznick et al 2007).…”
Section: Introductionmentioning
confidence: 99%
“…Rectal temperatures were maintained at ∼37°C during surgery and ischemia with an automated temperature control feedback system. Due to weight adjusted variation in vessel diameter, 0.21 mm and 0.23 mm siliconecoated sutures were used in mice weighing <30 g and >30 g, respectively, to achieve equivalent occlusion, as described previously (52). Sham-operated animals underwent the same surgical procedure, but the suture was not advanced into the middle cerebral artery.…”
Section: Methodsmentioning
confidence: 99%